The doctoral journey as an emotional, embodied, political experience
1 online resource
Keywords: "The Doctoral Journey as an Emotional, Embodied, Political Experience is the first text of its kind to capture stories of involvement in doctoral journeys from students, supervisors, and examiners. Drawing from experiences across a variety of disciplines in the social sciences, medical sciences, education and the humanities, these stories share a keenness to demonstrate the ways in which this journey is emotional (rather than detached), embodied (rather than separated), and political (rather than having no relationship to politics). The journey metaphor is often adopted to describe and explore the PhD process. However, this journey is usually only seen from the perspective of the doctoral candidate. This implies that it is only the student that learns, develops, and reflects. This is clearly not always (maybe never) the case. The suggestion that the candidate 'learns' whilst the supervisors 'teach' harks back to traditional masculinist educational approaches and neglects the reciprocal knowledge-sharing process between student and supervisor. Similarly, the prescription that relationships between all concerned remain 'professional' and removed, rather than in any way intimate, suggest an unrealistic acceptance of an scientific, detached objective agenda rather than an emotional, embodied, political, and holistic approach to research. The contributions to this book extend the journey metaphor to additionally consider the experiences of supervisors and examiners, including the joint, collaborative journey of the 'team' (the candidate, their supervisors, and their examiners). This provides a challenge to traditional understandings of the doctoral process and offers implications for future reflection and practice. This book is therefore an invaluable resource for doctoral students, supervisors, examiners, and readers interested in pedagogy and educational practice"--